Regulatory issues related to the use of sodium hypochlorite solutions in endodontics - Peters, Ove A.; Ballal, Nidambur V.; Abe, Shu; De Deus, Gustavo; Gündoğar, Mustafa; Camilleri, Josette; Zehnder, Matthias (My University, 2025)
Aim: To assess the regulation of sodium hypochlorite (NaOCl) solutions for endodontic usage in some of the world's main dental markets, in view of the European Union's recent move to classify antimicrobial root canal irrigants as high-risk devices under their Medical Device Regulation (MDR). Methodology: The authors consulted legal texts available online and communicated with local health authorities wherever necessary to assess into which medical device category NaOCl solutions intended for endodontic application were subsumed. Furthermore, it was investigated whether there were sources outside the dental market to obtain NaOCl solutions for root canal treatments. Results: Upon completion of this text (mid 2024), NaOCl solutions for root canal irrigation had not been classified in the US and Canada, whilst in the European Union, they had just been upgraded to high-risk medical devices, with all the consequences for the dental supply market. This MDR rule was adopted by the EU's close trading partners, the United Kingdom, Switzerland and Turkey. In Japan, the legal hurdles were already high for manufacturers and importers of endodontic NaOCl solutions. Conversely, in China, these solutions were down-graded from a high-risk to a medium-risk status in 2017. A low-medium risk category was applied in the other countries under investigation, that is, Australia, India and Brazil. In some countries there was a possibility for dentists to procure plain NaOCl solutions from pharmacies. An alternative route to avoid buying NaOCl from dental suppliers was to use (household) bleach solutions for root canal irrigation wherever this practice was not prohibited explicitly. Conclusions: The legal situation to produce, import and use NaOCl solutions for root canal irrigation differs vastly around the globe. A sensible approach to regulate (yet not over-regulate) endodontic NaOCl solutions appears to be timely and necessary.
Keywords: Bleach; EU 2017/745; Medical Device Regulation; Pharmacy; Root Canal